On the verge of the tactile. A conversation with Richard Sennett - Bambó Naya, Raimundo; Díez Medina, Carmen (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2020)
In his London studio at Shaffron Hill, Richard Sennett shares his current concerns, from the transformation processes taking place in our cities, to the very future of our planet. The scope of Sennett’s thinking – encompassing everything from buildings themselves, to cities, to territories – focuses in this conversation around issues such as gentrification, tourism, urban borders and boundaries, and his desire for a more ‘tactile’ urbanism. His reflections attract the attention not only of architects but also of urban designers, sociologists, geographers and environmental engineers, addressing as they do, key themes such as the dangers of social homogenization, the forces of capitalism and the consequences of climate change. The interview clearly illustrates the shift in Sennett’s interest from urbanism per se, to the broader question of climate change and environmental sustainability.
Keywords: Porosity; Threshold; Boundary; Border; Gentrification; 'Tactile' Urbanism